Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum

Functionalized single-walled carbon nanohorns to reinforce sulfonated poly(ether ether ketone) electrolyte for direct methanol fuel cells - Turanelloormana, Parameswaran; Sarmah, Sudeshna; Torris, Arun; Bhat, Santoshkumar D.; Unni, SreeKuttan M. (ChemElectroChem, 2020)
Carbon-nanomaterial-based additives are promising materials for improving the physicochemical properties of sulfonated polyether ether ketone (sPEEK) for its use as composite membrane electrolyte in direct methanol fuel cells (DMFCs). In this work, functionalized single-wall carbon nanohorns (f-SWNHs) are realized as an additive in sPEEK. The -COOH groups created on the SWNHs during peroxide treatment improve the dispersion of f-SWNHs in sPEEK and boost the proton conductivity, ion exchange capacity, mechanical properties and reduce the methanol permeability of the electrolyte. The composite membrane with 0.50 wt.% f-SWNHs shows improved electrochemical selectivity of 17.03x10(-4) Scm(-3)s and delivers the highest peak power density of 230 mW cm(-2)in DMFCs.
Keywords: carbon nanohorns; direct methanol fuel cells; membrane electrolyte; proton conductivity; sulfonated poly ether ether ketone

High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life